Periodontal status in male smokers visiting Hue University of Medicine and Pharmacy Hospital - Chau, Ngoc Phuong Thanh; Nguyen, Ngoc Tam Dan (Tạp chí Y Dược Huế, 2022)
Background: Many clinical studies, which were conducted to evaluate the association between smoking and periodontal diseases, have confirmed the harmful effects of smoking on oral health. Therefore, it is essential to properly assess the periodontal status and smoking habits to improve the effectiveness of interventions and disease prevention. Objective: This study aims to compare the prevalence and severity of periodontal disease in male smokers and male non-smokers visiting Hue University of Medicine and Pharmacy Hospital and to investigate the relationship between smoking and periodontal disease. Methods: A case- control study with 220 patients divided into two groups using a questionnaire to survey men aged 18-65 who have been smoking at the Department of Odonto-Stomatology, Hue University Hospital of Medicine and Pharmacy. Factors related to smoking behavior and clinical examination of periodontal status were adopted. Results: In the smokers group, the mean gingival index “GI” (0.647 ± 0.316), plaque index “PlI” (2.045 ± 0.447), “PPD” periodontal pocket depth (1.955 ± 0.470mm), clinical adhesion loss “CAL” (1.883 ± 0.771mm), “BOP” bleeding index (4.898 ± 3.117) with 95% confidence interval “CI”. The percentage of patients without periodontitis accounts for the majority compared with the remaining levels of periodontitis with values of smokers 67.27% and 99.36% non-smokers. There is a signficant difference in gingivitis and periodontitis in both study groups with p < 0.05. There is a correlation between periodontal indices and smoking indicators such as the number of cigarettes smoked per day, the number of years of smoking, and cumulative exposure p< 0.05. Conclusion: The study shows that the heavier the smoking status, the worse the periodontal condition. However, the more cigarettes smoked, the less gingivitis and bleeding gums.